1999
DOI: 10.1002/(sici)1521-4141(199911)29:11<3729::aid-immu3729>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Human tonsillar germinal center T cells are a diverse and widely disseminated population

Abstract: Germinal center (GC) T cells are a poorly investigated population with a unique helper-inducer memory phenotype. Murine GC T cells have been demonstrated to be oligoclonal and antigen specific. The aim of this study was to investigate the diversity of human tonsillar GC T cells. Immunohistochemistry with a panel of different TCRVbeta family antibodies and sequencing of TCRgamma gene rearrangements obtained from individual microdissected GC demonstrated local diversity of human tonsillar GC T cells. No evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Somatic hypermutation affects also the 5′-untranslated region of the BCL-6 gene, although the latter has only been shown for B-cells [19]. Whether or not somatic hypermutation occurs in human germinal center T-cells is controversial [5,9,23]. Bcl-6 expression is a recurrent finding in anaplastic large-cell lymphoma, in T-lymphoblastic lymphoma, and in a subset of PTCL as well as AILT.…”
Section: Discussionmentioning
confidence: 99%
“…Somatic hypermutation affects also the 5′-untranslated region of the BCL-6 gene, although the latter has only been shown for B-cells [19]. Whether or not somatic hypermutation occurs in human germinal center T-cells is controversial [5,9,23]. Bcl-6 expression is a recurrent finding in anaplastic large-cell lymphoma, in T-lymphoblastic lymphoma, and in a subset of PTCL as well as AILT.…”
Section: Discussionmentioning
confidence: 99%
“…T follicular helper cells (TFHs), for example, are a T cell subset that normally resides in the germinal centres of secondary lymphoid tissues [17]. Clones of TFHs are known to disseminate, so that a single TFH clone can be detected in both tonsils [18]. Small populations of TFHs in blood are referred to as circulating TFH (cTFH) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, 40–60% of the T cells in GC express Vα11/Vβ3 TCR during a PCC response [12–14]. Recent data from human tonsils analyzed with a panel of different TCR Vβ family antibodies demonstrated a local diversity among GC T cells [15]. These experiments showed that although there are antigen specific T cells in the GC they are rather diverse.…”
Section: Introductionmentioning
confidence: 99%